2001
DOI: 10.1523/jneurosci.21-22-08956.2001
|View full text |Cite
|
Sign up to set email alerts
|

In VivoImaging of Zebrafish Reveals Differences in the Spinal Networks for Escape and Swimming Movements

Abstract: Most studies of spinal interneurons in vertebrate motor circuits have focused on the activity of interneurons in a single motor behavior. As a result, relatively little is known about the extent to which particular classes of spinal interneurons participate in different behaviors. Similarities between the morphology and connections of interneurons activated in swimming and escape movements in different fish and amphibians led to the hypothesis that spinal interneurons might be shared by these behaviors. To tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
132
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 151 publications
(140 citation statements)
references
References 34 publications
8
132
0
Order By: Relevance
“…Moreover, the current results and a recent study in zebrafish (Ritter et al, 2001) both suggest that these shared and specialized subsets of spinal interneurons may to some extent be morphologically distinguishable. …”
Section: Morphological Comparisons To Dorsal Horn Cells In Other Studiessupporting
confidence: 69%
“…Moreover, the current results and a recent study in zebrafish (Ritter et al, 2001) both suggest that these shared and specialized subsets of spinal interneurons may to some extent be morphologically distinguishable. …”
Section: Morphological Comparisons To Dorsal Horn Cells In Other Studiessupporting
confidence: 69%
“…Such an organization has been observed in locusts, in which two different interneuron pools that control walking and flight converge on the same (bifunctional) muscles (Ramirez and Pearson, 1988). In vivo calcium imaging experiments in zebrafish spinal cord have also demonstrated that two different sets of interneurons drive swimming and escape behaviors, suggesting that dedicated circuitry is also used by vertebrates (Ritter et al, 2001).…”
Section: Introductionmentioning
confidence: 83%
“…Sensory stimuli that elicit escape responses are diverse but typically abrupt, such as a looming visual stimulus, a sudden pulse of vibration, or sudden mechanical stimulus on the head or body (Grillner et al 1998, Bosch et al 2001, Ritter et al 2001, Rossignol et al 2006. These stimuli rapidly activate brainstem neurons, which excite spinal cord neurons that generate a rapid tail thrust.…”
Section: Why Do Fishes Swim Away When Hooked?mentioning
confidence: 99%
“…These stimuli rapidly activate brainstem neurons, which excite spinal cord neurons that generate a rapid tail thrust. Activation of sustained swimming is produced by a network of spinal cord neurons known as the swimming pattern generator, which is regulated by neurons in the lower brainstem, that control the onset, offset, and speed of swimming (Grillner et al 1998, Ritter et al 2001, Rossignol et al 2006.…”
Section: Why Do Fishes Swim Away When Hooked?mentioning
confidence: 99%